2021
DOI: 10.4103/joacp.joacp_289_18
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dexmedetomidine on characteristics of ultrasound-guided supraclavicular brachial plexus block with levobupivacaine-A prospective double-blind randomized controlled trial

Abstract: Background and Aims: Levobupivacaine, a less cardiotoxic s-isomer of bupivacaine, is proved to be similar to bupivacaine, hence, proposed as a safer alternative for nerve blocks. We aimed to evaluate the effect of perineural and intravenous dexmedetomidine on characteristics of ultrasound-guided supraclavicular brachial plexus block (BPB) performed with levobupivacaine. The aim of this study is to evaluate the effect of perineural and intravenous dexmedetomidine on characteristics of ultrasound-gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…Moreover, Nazir also included a sedation score in the evaluation, and the results suggested that dexmedetomidine could increase the postoperative sedation effect. Reddy et al 50 compared the intravenous infusion of dexmedetomidine with the adjuvant of 0.5% lebupivacaine (1 μg/kg) in suclavicular brachial nerve block. The results revealed that sensory and motor blocks acted more quickly in the perineural group, with longer duration and analgesia than intravenous dexmedetomidine.…”
Section: Application Of Dexmedetomidine In Peripheral Nerve Blockmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Nazir also included a sedation score in the evaluation, and the results suggested that dexmedetomidine could increase the postoperative sedation effect. Reddy et al 50 compared the intravenous infusion of dexmedetomidine with the adjuvant of 0.5% lebupivacaine (1 μg/kg) in suclavicular brachial nerve block. The results revealed that sensory and motor blocks acted more quickly in the perineural group, with longer duration and analgesia than intravenous dexmedetomidine.…”
Section: Application Of Dexmedetomidine In Peripheral Nerve Blockmentioning
confidence: 99%
“… 145 Thus, a dose of dexmedetomidine of 1 μg/kg provides an optimal balance between adequate postoperative analgesia and the adverse effects of peripheral nerve block. 50 , 146 …”
Section: Recommendations For Peripheral Nerve Blocksmentioning
confidence: 99%
See 1 more Smart Citation
“…In 161 studies, patients received a supraclavicular brachial plexus block, 26,29–160 in 40 studies, patients received an axillary brachial plexus block, 24,27,161–198 in 28 studies, an interscalene block was performed, 25,199–220 in 11 studies, patients received an infraclavicular brachial plexus block, 221–231 one study used a coracoid approach to brachial plexus block 232 and one study used a suprascapular combined with axillary nerve block 233 . A detailed description of included studies is presented in the supplemental content (supplemental table 3, http://links.lww.com/EJA/A839).…”
Section: Resultsmentioning
confidence: 99%